Sedimentary record of a Pleistocene ice-sheet interlobate zone (NE Poland) - Gruszka, Beata; Morawski, Wojciech; Zieliński, Tomasz (Wydawnictwo Naukowe UAM, 2012)
Well developed NE-SW trending corridors of outwash in NE Poland are associated with a series of lakes with a similar direction of elongation. The glaciofluvial corridor under study consists of parallel ridges with associated channels and kames. The deposits are flanked by till and hummocky terrain. The gravel ridges are composed of sand and gravel deposits that are cross-stratified, massive or graded, and that contain cut-and-fill structures and large intra-clasts of sand and gravel. Locally the deposits show normal faults. The succession of one of the ridges is interpreted to reflect the infilling of a braided channel in a crevasse. Sedimentation took place in some phases when the ice-sheet regime changed from active to stagnant. Sandy-gravel ridges occur within this complex perpendicular to the Weichselian icesheet margin. The corridor is interpreted as an interlobate area in the zone between the Warmia and Mazury ice lobes. The braided- channel deposits are not comparable to typical Polish sandurs. The lithofacies characteristics show higher energy conditions, and the channels are deeper than those typical of Pleistocene lowland sandurs. The sand and gravel ridges are interpreted as interlobate eskers.
Keywords: Interlobate sedimentation; Outwash deposits; Esker; Weichselian